Implementation of management science in physical education subjects: A systematic literature review - Ridha, Sahbana; Akbar, Muhammad Army; Fadillah, Muhammad; Pebriyandi, Pebriyandi; Basuki, Sunarno; Arifin, Syamsul (Jurnal Patriot, 2024)
Problems: There is still a lack of research that focuses on identifying the implementation of management science in physical education. Addressing this gap is crucial as it can lead to improved student outcomes and more efficient use of resources. Furthermore, optimizing physical education through management science can contribute to a more comprehensive educational experience, emphasizing the importance of physical activity on students' performance and well-being. Purpose: The primary aim of this systematic literature review is to generate practical recommendations that will empower educators and policymakers to optimize physical education. By conducting a comprehensive analysis, this research seeks to offer valuable guidance for teachers in curriculum design, class management, and the effective evaluation of physical education programs. Additionally, it is advisable to incorporate these implications into the conclusion section of the work. Methods: This research uses the PICO method which the author applies in searching articles to reveal new findings. In the data collection stage, articles were collected via Google Scholar and Crossref. Results: The author found 954 articles resulting from searches via Google Scholar and Crossref via Publish or Perish, then extracted until the author found 7 articles that met all the. Conclusion: Based on a comprehensive analysis of seven research articles, it is evident that the application of management science in physical education is predominantly driven by educators across various educational levels. These findings underscore the pivotal role of effective management by physical education teachers, encompassing learning planning, implementation, and evaluation, to significantly enhance student learning outcomes. Despite the limited number of relevant studies, the results highlight the critical importance of further exploring the application of management in physical education. Further research is needed on various aspects of the application of management science in physical education. Collaboration between physical education experts and management can produce innovative interdisciplinary approaches in the development and implementation of physical education programs